Percutaneous treatment of traumatic talus extrusion: a case report. - Calabrò, Davide; Meliadò, Giuseppe; Biasi, Michele; Topa, Gaetano; Campo, Francesco; Fusini, Federico (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of work: Total traumatic extrusion of talus with interruption of all ligaments (missing talus) is a very rare injury. We represent the case of a 44-years-old male who reported total extrusion of talus and Lisfranc dislocation after a motorbike accident. This rare injury has a wide choice of treatment but usually there is not a successful functional restore. Methods: We decided to treat the patient with an immediate reimplantation of extruded talus using 3 Kirschner wires and antibiotic therapy. We performed a temporary fixation of talus with calcaneus, tibia and scaphoid. Results: Usually, this kind of injuries are treated with a tibiocalcaneal arthrodesis and show common complications such as avascular necrosis and infection. Against our expectations we managed to treat successfully our patient. Conclusions: After 5 years of follow up the patient reported good clinical outcomes without performing arthrodesis and recording major complications.